Virtual screening of natural products inspired in-house library to discover potential lead molecules against the SARS-CoV-2 main protease. Issue 5 (24th March 2023) - Garg, Aakriti; Goel, Narender; Abhinav, Nipun; Varma, Tanmay; Achari, Anushree; Bhattacharjee, Pinaki; Kamal, Izaz Monir; Chakrabarti, Saikat; Ravichandiran, Velayutham; Reddy, Araveeti Madhusudhana; Gupta, Sreya; Jaisankar, Parasuraman
Abstract: SARS-CoV-2, a new coronavirus emerged in 2019, causing a global healthcare epidemic. Although a variety of drug targets have been identified as potential antiviral therapies, and effective candidate against SARS-CoV-2 remains elusive. One of the most promising targets for combating COVID-19 is SARS-CoV-2 Main protease (M pro, a protein responsible for viral replication. In this work, an in-house curated library was thoroughly evaluated for druggability against M pro . We identified four ligands (FG, Q5, P5, and PJ4) as potential inhibitors based on docking scores, predicted binding energies (MMGBSA), in silico ADME, and RMSD trajectory analysis. Among the selected ligands, FG, a natural product from Andrographis nallamalayana, exhibited the highest binding energy of −10.31 kcal/mol close to the docking score of clinical candidates Boceprevir and GC376. Other ligands (P5, natural product from cardiospermum halicacabum and two synthetic molecules Q5 and PJ4) have shown comparable docking scores ranging −7.65 kcal/mol to −7.18 kcal/mol. Interestingly, we found all four top ligands had Pi bond interaction with the main amino acid residues HIS41 and CYS145 (catalytic dyad), H-bonding interactions with GLU166, ARG188, and GLN189, and hydrophobic interactions with MET49 and MET165 in the binding site of M pro . According to the ADME analysis, Q5 and P5 are within the acceptable range of drug likeliness, compared to FG and PJ4. The interaction stability of the lead molecules with viral protease was verified using replicated MD simulations. Thus, the present study opens up the opportunity of developing drug candidates targeting SARS-CoV-2 main protease (M pro ) to mitigate the disease. Communicated by Ramaswamy H. Sarma Abstract : UF0001